Correlation and Heritability Studies of Yield and Yield Related Traits in F5 Triticum aestivum Lines from a Cross Cv Fsd-08 Ã— Cv S-24 - Afzal, Shehrooz; Amir, Misbah; Qamar, Sanobar Shadab; Tariq, Ayesha; Javed, Muhammad; Zafar, Zafar Ullah; Athar, Habib ur Rehman (Journal of Cereal Research, 2021)
The heritability estimates give information about traits which are transferred from one generation to another generation, and it has important role in selection criteria to enhance the yield potential. The purpose of current study was to estimate heritability and genetic advance of F5 wheat lines derived from a cross of Faisalabad 2008 and S-24. Eight yield parameters were evaluated during the year 2019-20 in complete randomize design with five replicates. The results of ANOVA showed significant difference (P â‰¤0.001) in all studied traits. High broad sense heritability was observed for grain yield per spike (82.49%) followed by tillers per plant (81.77%) and spikelet per spike (76.65%). Moderate to low genetic advance was observed for all the traits except plant height (79.47%), and grain yield per spike have 73.10%. Grain yield have positive correlation with fertile tiller, 100 seed weight and grain yield per spike. The traits grain yield per spike, tillers per plant and spikelet per spike deserve more attention in future breeding programs for evolving better wheat yield.